Human umbilical cord mesenchymal stem cells alleviate fatty liver ischemia‐reperfusion injury by activating autophagy through upregulation of IFNγ - Xu, Chenhao; Fang, Xixi; Lu, Bei; Song, Yisu; Shu, Wenzhi; Lu, Zhengyang; Su, Renyi; Xiang, Ze; Xu, Xiao; Wei, Xuyong (Cell biochemistry and function, 2024)
Liver ischemia‐reperfusion injury (IRI) is an important factor affecting the prognosis of liver transplantation, and extended criteria donors (e.g., steatosis donor livers) are considered to be more sensitive to ischemia‐reperfusion injury in liver transplantation. Currently, the application of human umbilical cord mesenchymal stem cells (hMSCs) has great promise in the treatment of various injuries in the liver. This study aimed to investigate the therapeutic role and mechanism of hMSCs in fatty liver IRI. After more than 8 weeks of high‐fat chow feeding, we constructed a fatty liver mouse model and established ischemic injury of about 70% of the liver. Six hours after IRI, liver injury was significantly alleviated in hMSCs‐treated mice, and the expression levels of liver enzyme, inflammatory factor TNF‐α, and apoptotic proteins were significantly lower than those of the control group, which were also significant in pathological sections. Transcriptomics analysis showed that IFNγ was significantly upregulated in the hMSCs group. Mechanistically, IFNγ, which activates the MAPK pathway, is a potent agonist that promotes the occurrence of autophagy in hepatocytes to exert a protective function, which was confirmed by in vitro experiments. In summary, hMSCs treatment could slow down IRI in fatty liver by activating autophagy through upregulation of IFNγ, and this effect was partly direct. Significance statement This study demonstrated the important therapeutic role of human umbilical cord mesenchymal stem cells (hMSCs) in fatty liver ischemia‐reperfusion injury (IRI) and elaborated the mechanism of IFNγ in activating autophagy and thus playing a protective role, which is of positive significance for the study of functional protection and enhancement of transplanted donor liver.